Antropologia/Sittlichkeit: due scienze dell’Hegel ‘maturo’ per l’unico tragitto dalla necessità naturale alla libertà spirituale - Ricci, Vittorio (Revista Eletrônica Estudos Hegelianos, 2018)
The freedom is the absolute ‘keyword’ and the totalizing reality in Hegel’s thought, philosophical evolution and system. Its determination yields a continuous labor with several phases, corrections, new elaborations from the early formulations and drafts to the mature conceptions and writings. In spite of its polymorphous complexities, its fundamental and inescapable feature is the ‘ universal’  condition of spirit out of natural conditions, in the sense that spirit has to become nature to itself and in the same time its sole nature. This determination is possible only for and in the system, because the freedom is the a ‘ systematic’  process of various constitutive processes and its complete result. Sittlichkeit  is the item characterizing this highly complicate path faced by Hegel and representing also his philosophical production from its beginning to its end. The intricate enchainment between the consciousness and ethical entity including multifaceted forms of spiritual life has induced to start individualizing in the Sittlichkeit  the principle or ‘ Idea’  of an early, very promising ‘system’.  But only after facing consciousness’ essence and function inside the whole system, it  has been possible to grasp the nature of Seele  and so the anthropology, that is the true fulcrum of every systematic sections and their same justification, so that the ethical in its any direction and declination has been properly clarified